THERAPEUTIC MANAGEMENT AND CHANGES IN THE ENDOMETRIUM OF REPEAT BREEDING COWS - PATEL, J A; DHAMI, A J; KAVANI, F S; PANCHAL, M T; GHODASARA, D J (The Indian Journal of Animal Reproduction, 2023)
The overall incidence of repeat breeding observed among 98 breedable Holestein Friesian (HF)animals of a farm was 40.82 % (n=40). These 40 repeat breeding cows were divided at random Indifferent groups with a view to evaluate the relative efficacies of different hormonal therapies at breedingtowards improving their reproductive efficiency over the control. The conception rate following i/m treatmentat the time of insemination with GnRH (Receptal, Busere/ln acetate, 0.02 mg), LH (Chorulon, 1500 IU)and Progesterone (Proluton depot, 500 mg) was 66.66, 83.33 and 50.00 %, respectively, with an overallmean of 66.66 % (12/18). This was significantly higher (P
Keywords: Endometrial biopsy; Hormonal therapy; Repeat breeding cows